Bearing witness: an analysis of the reporting and the reception of news about distant suffering in the light of John Howard Yoder‘s work on witness - Richards, Amy Diane (The University of Edinburgh, 2010)
In this thesis I analyse the reporting and the reception of news about distant suffering in the light of John Howard Yoder‘s work on witness. Studies of news reporting about foreign wars, genocide and disasters commonly conclude that the practice of bearing witness to distant suffering contributes to a context where both journalists and spectators appear to have limited moral agency. I argue that the practice of bearing witness has ethical significance for those actively engaged in bearing witnessing. In his work on Christian witness, Yoder demonstrates how witness can be understood as a method for moral reasoning. I assert that Yoder‘s argument presents a fruitful approach for interdisciplinary consideration of the ethical significance found in the practice of bearing witness to distant human suffering. In chapter one, I lay the foundation of my investigation into the ethical agency involved in bearing witness. John Howard Yoder‘s theological approach to social ethics provides that foundation. Central to Yoder‘s claim that witness is a form of ethics, is the premise that presence testifies. Yoder calls this the 'phenomenology of social witness‘. Yoder‘s work opens new ways in which to ask questions about the practice of bearing witness as a form of social ethics. It is from this foundation that I begin to ask questions about the news media practice of bearing witness to distant suffering, the subject of chapter two. Media practices are social practices that involve a dense interaction of many layers of society. In the media practice of witnessing distant suffering, governments, charities, news media organisations, and audiences are all involved in what I call the social formation of the Global Samaritan. The foundational work on Yoder in chapter one allows me to ask the question: How is the Global Samaritan a presence, and to what does this presence testify? In chapters three and four, I focus on two of the prominent groups which contribute to the formation of the Global Samaritan: audiences and foreign correspondents. News audiences as moral agents already seem a problem for Yoder‘s claim that presence testifies. Do audiences who bear witness to distant suffering have moral agency? How can the amorphous and fleeting presence of television, internet, or twitter audiences testify? In the chapter on audiences, the initial claim regarding presence makes for an important investigation into how audiences can potentially move beyond mere spectatorship and towards participation in care for the suffering. Foreign correspondents bearing witness to distant suffering do not face the same obstacles to testifying as audiences do. After all, foreign correspondents are often live, on-the-scene of extraordinary circumstances of suffering. The danger and risks foreign correspondents face in order to report live from scenes of devastation and disaster testify to the fact that the situation is indeed dangerous and causing suffering. Yoder‘s claim that presence testifies is a claim strongly paralleled within the tradition of investigative journalism. In chapter four, I investigate the ethical function of foreign correspondent presence. I consider the foreign correspondent‘s dual role as the proxy 'eyes and ears‘ of the public and the proxy voice for those without a voice. Through these two roles, I explore major concepts involved in the practice of investigative journalism. One prominent issue I explore is the tension between the principles of a liberal democratic press and the practice of frontline reporters live, on-the-scene of extraordinary and extreme situations. In the final chapter, chapter five, I focus on the experience of three frontline reporters bearing witness to human suffering. BBC [British Broadcasting Company] reporter John Simpson‘s reflections on his coverage of the beginning of the Iraq War illustrate the importance of bearing witness as involving real presence on location. Norwegian freelance reporter Ǻsne Seierstad‘s reflections on covering the Iraq War from Baghdad further contributes to the concept of 'being there‘ as central to bearing witness. Focus on Seierstad also furthers discussion on women reporters bearing witness to war. The third reporter I highlight is BBC reporter Fergal Keane. I focus on his reflections covering the Rwandan genocide to illustrate how the claim to bearing witness involves more than spectatorship, but often involves participation. I conclude with an analysis of the media practice of bearing witness, involving the range of reporter presence to the quasi-presence of the audience, in the light of John Howard Yoder‘s claim that bearing witness is a form of social ethics.
Keywords: Yoder, John Howard; spectatorship; distant suffering; war correspondent